Pendampingan Pembuatan Pencatatan Pembukuan Sederhana Pada Panti Asuhan Batu Penjuru Di Kulon Progo Provinsi Daerah Istimewa Yogyakarta - Tri Handayani; Rochmad Bayu Utomo (Jurnal Pengabdian Bersama Masyarakat Indonesia, 2023)
This community engagement research aims to provide assistance in simple bookkeeping to orphanages with the objective of improving transparency, accuracy, and financial management effectiveness. The assistance method involves a series of activities, including basic training in simple bookkeeping, the development of easily comprehensible financial report formats, and the provision of guidance and direct supervision in day-to-day financial record-keeping. Evaluation and monitoring are conducted throughout the assistance period to measure progress and ensure alignment with the specific needs of the orphanages. The research findings indicate that the provision of simple bookkeeping assistance offers significant benefits to orphanages. The financial recording skills of the administrators improve, leading to more accurate and trustworthy financial reports. Furthermore, transparency in financial management increases, thereby fostering trust and participation from relevant stakeholders such as donors and regulatory bodies. The implementation of a simple bookkeeping system also aids administrators in making better decisions based on the available financial information